Courtroom communication: identification of the communication characteristics of criminal trials in Indonesian courts - Widodo, Aan (Frontiers in Communication, 2025)
The courtroom in Indonesia functions not only as a formal legal setting but also as a socio-communicative arena where judges, prosecutors, defense lawyers, witnesses, and defendants interact under strict procedural and cultural norms, shaping justice, transparency, and public trust. This study employed a qualitative case study approach to analyze courtroom communication in Indonesian criminal trials, with data collected through interviews with nine informants (judges, prosecutors, defense lawyers, a witness, and a defendant), observations of three trials at the Bekasi District Court, and document analysis. Using thematic analysis involving coding, categorization, interpretation, and conclusion, the study identified two dominant communication flows: one-way communication, such as judicial instructions and verdict delivery, and multi-directional communication, such as examinations and cross-examinations. Furthermore, six communication characteristics were found: professional, hierarchical, confrontational, investigative, adversarial, and supportive, illustrated by examples such as judges’ clarifying questions, prosecutorial challenges, and empathetic accommodations for vulnerable witnesses. Theoretically, the study advances socio-legal communication research by integrating dimensions of authority, contestation, and fairness in courtroom interaction, while practically, it provides insights for legal practitioners to strengthen communication strategies that enhance effectiveness, fairness, and legitimacy in judicial processes, thereby reinforcing public trust in Indonesia’s justice system.